Integrative methodological platform to reconstruct macrounits of discourse in functioning: Belarusian case study - Oukhvanova, Irina; Yelsukova, Natallia (Przegląd Wschodnioeuropejski, 2020)
Discourse Linguistics, an applied field of research focused on complex contentmacrostructures open to multiple transformations in functioning, currently raises such a research problem as how to cope with its multidimensional units staying focused on its holistic nature. For this integrative methodological platforms are introduced and tested. The authors, accepting discourse community representations built within the composites of the image-making discourse type as a forefront research object, introduce and verify such kind of a platform both theoretically and practically (on the discourse of respondents who represent one of currently built Belarusian discourse communities). The approaches inbuilt into the platform are Tartu-Moscow semiotic school (Lotman 2005, 205-226), French school of discourse analysis (Maingueneau 2002, 185-190), the causal-genetic approach of discourse modeling / CGA (Oukhvanova 2017, 5-16), and Swales’ approach to discourse community research (2016).